Efektivitas Media Pembelajaran Interaktif Berbasis Genially dalam Meningkatkan Hasil Belajar Siswa Sekolah Menengah Pertama - Dinda; Rahayu, Puji (Program Studi Pendidikan Matematika FIP UNHASY, 2026)
This study aims to evaluate the effectiveness of Genially-based interactive learning media in improving junior high school students' mathematics learning outcomes in Social Arithmetic. The background of this study is based on the need for digital learning media that can present abstract concepts more clearly and attractively. This study utilizes a quantitative approach and a One-Group Pretest–Posttest pre-experimental design. The sample used for the study was 31 seventh-grade students. The research instrument was a pretest and posttest given before and after the Genially-based learning intervention. To determine the effectiveness of improving learning outcomes, data were analyzed using the N-Gain test. The results showed an increase in students' total scores in the pretest from 1,128 to 2,261 in the posttest, with an average increase of 47.87 points. The N-Gain value of 0.75 is included in the high category, which means that the use of Genially is effective in improving students' learning outcomes in Social Arithmetic. These results support the idea that technology-based interactive learning methods can significantly improve students' understanding of mathematical concepts. This study shows that Genially is worth incorporating into mathematics learning because it can improve students' motivation, their understanding, and their learning outcomes.